Review of the Durability of Polymer Electrolyte Membrane Fuel Cell in Long-Term Operation: Main Influencing Parameters and Testing Protocols - Huu Linh Nguyen; Jeasu Han; Xuan Linh Nguyen; Sangseok Yu; Young-Mo Goo; Duc Dung Le (Energies, 2021)
Durability is the most pressing issue preventing the efficient commercialization of polymer electrolyte membrane fuel cell (PEMFC) stationary and transportation applications. A big barrier to overcoming the durability limitations is gaining a better understanding of failure modes for user profiles. In addition, durability test protocols for determining the lifetime of PEMFCs are important factors in the development of the technology. These methods are designed to gather enough data about the cell/stack to understand its efficiency and durability without causing it to fail. They also provide some indication of the cell/stack’s age in terms of changes in performance over time. Based on a study of the literature, the fundamental factors influencing PEMFC long-term durability and the durability test protocols for both PEMFC stationary and transportation applications were discussed and outlined in depth in this review. This brief analysis should provide engineers and researchers with a fast overview as well as a useful toolbox for investigating PEMFC durability issues.